Toward an effective delivery system of a microbial sink of the uremic toxin, p-cresol; an in vitro study with Thauera aminoaromatica S2 - Saingam, Prakit; Rasyid, Rosita; Abrahamson, Britt; Lie, Thomas J.; Godfrey, Bruce J.; Himmelfarb, Jonathan; Winkler, Mari K. H. (Frontiers in Microbiology, 2025)
Individuals with chronic kidney disease (CKD) suffer from uremia, a condition characterized by the accumulation of uremic toxin in the blood. The aromatic uremic toxin p-cresol, a byproduct of tyrosine fermentation in the gut, binds to plasma albumin and cannot be removed with dialysis. However, the ingestion of densified p-cresol degrading microorganisms encapsulated in protective hydrogel beads could provide a therapeutic benefit by removing p-cresol from the colon. In this study the p-cresol degradation capacity of a known anaerobic, p-cresol degrading microorganism, T. aminoaromatica S2, encapsulated in polyvinyl alcohol and sodium alginate (PVA/SA) hydrogels was evaluated as a potential oral delivery method for intestinal p-cresol removal. Planktonic degradation was induced through prior p-cresol exposure, yielding a 100% removal efficiency at a rate of 92 nmol (Log CFU)-1 h-1 when exposed to 1.2 mM of p-cresol at 37°C. Increasing p-cresol concentrations inhibited p-cresol degradation. Hydrogel encapsulation of the bacteria supported high cell density packaging at 2.5 Log CFU (mL hydrogel)-1 and high activity right after hydrogel production, and more rapid activity than the planktonic cells, providing a powerful p-cresol-consuming microbial sink. Our experimental design mimicked distal colon conditions with an initial p-cresol level of 0.60 mM and at a pH 7 where the p-cresol degradation capacity of encapsulated culture was 2.3 × 103 nmol (Log CFU)-1 h-1. The encapsulation of 10-fold increased cell concentrations resulted in more than 2-fold increased degradation rates. With the cell densification, the estimated daily hydrogel intake could be reduced from 134 mL to 58 mL to match daily exposure, thereby achieving mass balance. The effective removal rates were due to well distribution of bacteria cells within the hydrogels. The hydrogels with p-cresol pre-induced biomass showed immediate p-cresol removal even at p-cresol higher than 1.0 mM concentration. The current study demonstrated the potential application of encapsulated T. aminoaromatica S2 for the removal of colon p-cresol hence offloading the kidney from processing protein-bound uremic toxins. Further research in hydrogel design could yield efficient removal as well as cell encapsulation.